2019
DOI: 10.1002/jmri.26787
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Tumor Mechanics by MR Elastography at Different Strain Levels

Abstract: Background Malignant tumors are associated with increased tissue rigidity, which can be an indicator of tumor progression. MR elastography (MRE) has the potential to study the variations of tumor mechanical properties. ex vivo studies have shown the ability of MRE to assess increase of mechanical properties; nevertheless, it has not yet been observed in vivo. Purpose To propose a method to assess the increase in mechanical properties of tumors in vivo under static external compression using MRE. Study Type Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Due to changes in the cellular and extracellular matrix components, the compression of the tumor and the host tissue changes during tumor progression. These effects can result in changes in the stiffness of the tumor [ 26 , 32 , 91 , 92 ]. The incorporation of temporal variations in the elastic properties would be expected to change our results quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Due to changes in the cellular and extracellular matrix components, the compression of the tumor and the host tissue changes during tumor progression. These effects can result in changes in the stiffness of the tumor [ 26 , 32 , 91 , 92 ]. The incorporation of temporal variations in the elastic properties would be expected to change our results quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors reported complex shear modulus for other orthotopic tumours including BT-474 (2.9 ± 0.2 m s −1 ), PANC1 (3.3 ± 0.2 m s −1 ), and other intracranial tumours from GTML/Trp53 (2.1 ± 0.2 m s −1 ) to U87 MG (2.5 ± 0.2 m s −1 ), and finally subcutaneous SW620 (2.3 ± 0.2 m s −1 ) (Li et al 2014b ). Page et al ( 2019 ), reported the shear elastic modulus of SA-LIV tumours using MR elastography at 600 Hz (1.3 m s −1 ). Ahmed et al ( 2020b ) used STL-SWE, an ARFI based ultrasound shear wave imaging modality to measure the shear wave speed of PDAC xenograft tumours (2.3 ± 0.5 m s −1 ) in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although the first represents a perfect soft solid, the second has strongly attenuating properties. 27 Magnetic resonance elastography holds great potential for the mechanical, noninvasive characterization of tumors in patients, 39 particularly for image-based quantification of solid stress 40,41 and tissue fluidity. 30,42 Current limits of MRE are related to its relatively low spatial resolution for the assessment of tumor heterogeneity as well as stability issues due to noise and possible negative interferences of propagating waves.…”
Section: Magnetic Resonance Elastographymentioning
confidence: 99%